Readout circuit for conductivity measurement with parasitic resistance compensation - Katman, Ratchanoo; Petchmaneelumka, Wandee; Rerkratn, Apinai; Kaewpoonsuk, Anucha (My University, 2018)
This paper presents a simple method based on commercially available current feedback operational amplifiers (CFOAs) to realize the readout circuit for measuring the solution conductivity including the parasitic resistance in the electrode sensor. The enhanced readout circuit for conductivity measurement in electrolyte solution, compared with the conventional readout circuit using the op-amp inverting amplifier, offers a technique for the parasitic resistance compensation to improve the linearity of the measurement results. The proposed readout circuit provides the digital output which is directly proportional to the conductivity of electrolyte solution. The experimental verification and the measured results of the method are included in this paper.
Keywords: Conductivity measurement; Parasitic resistance compensation; Readout circuit